JADID PERIODICALS AND SOCIAL DEVELOPMENT IN EARLY TWENTIETH-CENTURY TURKESTAN (World Bulletin of Education and Learning, 2026)
This article surveys how Jadid intellectuals used newspapers and magazines as a practical instrument of social development in Turkestan and neighboring protectorates in the early twentieth century. Rather than treating “the press” as a neutral channel, I approach it as a social technology that reorganized who could speak publicly, what counted as credible knowledge, and how reform proposals circulated beyond narrow scholarly circles. Drawing on scholarship on printing and reform under Russian rule, I show that Jadid publishing expanded the social reach of enlightenment agendas by normalizing public debate about schooling, literacy, economic skills, ethics, and community responsibilities, while also exposing reformers to licensing regimes, censorship, and rapid closures. The short life of many periodicals did not mean weak influence: the press created reusable formats – editorials, appeals, polemics, and serialized instruction – that helped turn “education” from a private virtue into a collective project. The discussion ends by noting evidentiary limits and proposing cautious interpretation.
Keywords: Jadidism, periodical press, Turkestan, social reform, enlightenment discourse, colonial censorship, literacy, public debate, national consciousness, early Uzbek journalism.